Peran Good governance dalam Meningkatkan Pembangunan Daerah di Sumatera Barat: Studi Literatur - Azri Triana Putri; Sri Permata Putri; Boni Saputra (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Regional development constitutes a strategic agenda within the decentralization framework that demands good governance as its primary prerequisite. This article aims to analyze the role of good governance principles in improving the quality of regional development in West Sumatra Province, identify the obstacles encountered in its implementation, and formulate relevant policy recommendations. This study employs a literature review method by collecting, examining, and analyzing various sources, including national and international scientific journals, books, research reports, official regional government documents, and legislation related to good governance and regional development. The findings indicate that the implementation of good governance in West Sumatra possesses a distinctive characteristic, namely the synergization of good governance principles with the Minangkabau customary philosophy in the management of Nagari governance. The regional government plays strategic roles as an entrepreneur, coordinator, facilitator, and stimulator in promoting sustainable development. Nevertheless, the implementation of good governance still faces several structural challenges, such as low levels of public participation, weak partnership between the legislative and executive branches, and tension between central and regional interests. Consistent strengthening of the principles of transparency, accountability, participation, and the rule of law is key to achieving effective, equitable, and sustainable regional development in West Sumatra.